Aripiprazole lai two-injection start in a 16 year-old with Schizophrenia. (1st June 2022) - Marpepa, B.; Appignanesi, C.; Orsolini, L.; Volpe, U.; Salvi, V.
Abstract : Introduction: Aripiprazole LAI is approved for the treatment of schizophrenia in adults. Recently, Europe and Canada approved the use of the two-injection start (TIS) regimen: two separate injections of 400 mg long-acting aripiprazole along with a single 20 mg dose of oral aripiprazole. Aripiprazole showed efficacy in the treatment of adolescents with acute schizophrenia in several controlled trials, leading to its approval for 13-17 year-old adolescents with schizophrenia by the EMA. However, the LAI formulation still remains off-label in adolescents. Objectives: To demonstrate the efficacy and safety of the TIS regimen of aripiprazole LAI formulation in a 16 year-old adolescent with schizophrenia. Methods: We evaluated the symptoms of schizophrenia and general severity by means of the PANSS and CGI scales. The scales were administered at hospital admission, after 3 weeks, 5 weeks, and at 4-weeks follow-up. Results: At the admission the patient PANSS total score was 136, the CGI score of 7. Aripiprazole was started and up-titrated to 30 mg/day. After 3 weeks, the positive symptoms were significantly reduced; due to the persistence of negative symptoms, clozapine 100 mg/day was added. At week 5 the PANSS total score decreased to 81. Due to poor insight we proposed aripiprazole LAI with the two-injection start. One month later, global functioning and illness insight improved; PANSS score was 43, CGI score 2. There was no evidence of akathisia or other side effects. Conclusions: Aripiprazole LAI showed good efficacy and tolerability in an adolescent with schizophrenia. The two-injection start regimen was a safe and viable option. Disclosure: No significant relationships.